Human apical-out nasal organoids reveal an essential role of matrix metalloproteinases in airway epithelial differentiation - Liyue Li; Linyi Jiao; Danni Feng; Yizhang Yuan; Xiaoqian Yang; Jian Li; Dong Jiang; Hexin Chen; Qingxiang Meng; Ruchong Chen; Bixing Fang; Xuenong Zou; et al. (Nature Communications, 2024)
Abstract Extracellular matrix (ECM) assembly/disassembly is a critical regulator for airway epithelial development and remodeling. Airway organoid is widely used in respiratory research, yet there is limited study to indicate the roles and mechanisms of ECM organization in epithelial growth and differentiation by using in vitro organoid system. Moreover, most of current Matrigel-based airway organoids are in basal-out orientation where accessing the apical surface is challenging. We present a human apical-out airway organoid using a biochemically defined hybrid hydrogel system. During human nasal epithelial progenitor cells (hNEPCs) differentiation, the gel gradually degrade, leading to the organoid apical surfaces facing outward. The expression and activity of ECM-degrading enzymes, matrix metalloproteinases (MMP7, MMP9, MMP10 and MMP13) increases during organoid differentiation, where inhibition of MMPs significantly suppresses the normal ciliation, resulting in increased goblet cell proportion. Moreover, a decrease of MMPs is found in goblet cell hyperplastic epithelium in inflammatory mucosa. This system reveals essential roles of epithelial-derived MMPs on epithelial cell fate determination, and provides an applicable platform enabling further study for ECM in regulating airway development in health and diseases.